Self-Healing Coatings Based on Stimuli-Responsive Release of Corrosion Inhibitors: A Review - Zhang, Yue; Yu, Mei; Chen, Chao; Li, SongMei; Liu, JianHua (Frontiers in Materials, 2022)
Corrosion inhibitors loaded in coatings promote the protection performance of coatings, avoid the local corrosion of metal substrate, and endow the self-healing properties of the coatings. The stimuli-responsive release of corrosion inhibitors, which generally achieved by loading corrosion inhibitors in containers, is the key to the self-healing and long-term protection of the coatings. The loading and release methods of corrosion inhibitors were discussed in the paper. Two kinds of loading methods of corrosion inhibitors are reviewed first, which are one-step synthetic methods and multi-step synthetic methods. Then the releasing methods of corrosion inhibitors, which can be achieved by intrinsic properties and surface modification of containers, were summarized.